2008
DOI: 10.1037/1099-9809.14.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Gendered racism, psychological distress, and coping styles of African American women.

Abstract: This study explores the relationship of the accumulative effect of gendered racism, the discrimination felt by African American women, on psychological distress. The study also explores whether coping serves as a mediating variable between gendered racism and psychological distress. Over 300 African American women participated in the study and were administered the Symptoms Checklist 90, a revised version of the Schedule of Sexist Events, and the Africultural Coping Styles Inventory. A positive significant rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
327
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(354 citation statements)
references
References 29 publications
26
327
1
Order By: Relevance
“…This procedure was adopted to assess the use of culture-specific strategies in response to racismrelated experiences. In a study conducted by Thomas et al (2008) to examine culture-specific strategies in response to gendered racism for African American women, the authors reported that they did not request that participants respond to the open-ended question by recalling experiences of gendered racism, a shortcoming they noted. Thus, having participants explicitly recall experiences of racism in the current study served to address this particular limitation.…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure was adopted to assess the use of culture-specific strategies in response to racismrelated experiences. In a study conducted by Thomas et al (2008) to examine culture-specific strategies in response to gendered racism for African American women, the authors reported that they did not request that participants respond to the open-ended question by recalling experiences of gendered racism, a shortcoming they noted. Thus, having participants explicitly recall experiences of racism in the current study served to address this particular limitation.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Although multiple studies have served to pinpoint the types of strategies used by African American women to cope with race-related incidents (e.g., Krieger, 1990;Thomas, Witherspoon, & Speight, 2008), little information exists regarding the ways in which coping efforts moderate the relationship between race-related stress and psychological symptoms for this population of women. The few studies (e.g., Abrums, 2004) that have considered the influence of coping strategies on race-related mental health effects for this group of women have been qualitative.…”
Section: Coping With Race-related Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 Men and women differ in using coping styles in their daily lives. 35,78 Overall, men more frequently use confrontational coping, 79 while women have a higher tendency to avoid stressors. 78 Compared to women, men also have a higher tendency in acting out their stress 80 and externalizing their emotions.…”
Section: Assarimentioning
confidence: 99%
“…35,78 Overall, men more frequently use confrontational coping, 79 while women have a higher tendency to avoid stressors. 78 Compared to women, men also have a higher tendency in acting out their stress 80 and externalizing their emotions. 81 These findings may explain why implicit bias is higher in White men than White women.…”
Section: Assarimentioning
confidence: 99%